(untitled) (Global Journal of Medical Research, 2023)
Introduction Inappropriate management of splenic trauma is related to high rates of morbidity and mortality and an effective understanding of its mechanisms is vital Closed abdominal or thoracoabdominal trauma such as localized contusions from various incidents is typically the cause of splenic injuries Splenic trauma must be promptly evaluated in the context of urgency and a surgical approach must be performed according to the degree of injury Methods This is a retrospective quantitative and cross-sectional analysis of the medical records of operated-on patients